Ultrasensitive amplification refractory mutation system real-time PCR (ARMS RT-PCR) assay for detection of minority hepatitis B virus-resistant strains in the era of personalized medicine. - Ntziora, Fotinie; Paraskevis, Dimitrios; Haida, Catherine; Manesis, Emanuel; Papatheodoridis, George; Manolakopoulos, Spilios; Elefsiniotis, Ioannis; Karamitros, Timokratis; Vassilakis, Alexis; Hatzakis, Angelos (J Clin Microbiol, 2013)
Resistance to antiviral treatment for chronic hepatitis B virus (HBV) has been associated with mutations in the HBV polymerase region. This study aimed at developing an ultrasensitive method for quantifying viral populations with all major HBV resistance-associated mutations, combining the amplification refractory mutation system real-time PCR (ARMS RT-PCR) with a molecular beacon using a LightCycler. The discriminatory ability of this method, the ARMS RT-PCR with molecular beacon assay, was 0.01 to 0.25% for the different HBV resistance-associated mutations, as determined by laboratory-synthesized wild-type (WT) and mutant (Mut) target sequences. The assay showed 100% sensitivity for the detection of mutant variants A181V, T184A, and N236T in samples from 41 chronically HBV-infected patients under antiviral therapy who had developed resistance-associated mutations detected by direct PCR Sanger sequencing. The ratio of mutant to wild-type viral populations (the Mut/WT ratio) was >1% in 38 (63.3%) of 60 samples from chronically HBV-infected nucleos(t)ide analogue-naive patients; combinations of mutations were also detected in half of these samples. The ARMS RT-PCR with molecular beacon assay achieved high sensitivity and discriminatory ability compared to the gold standard of direct PCR Sanger sequencing in identifying resistant viral populations in chronically HBV-infected patients receiving antiviral therapy. Apart from the dominant clones, other quasispecies were also quantified. In samples from chronically HBV-infected nucleos(t)ide analogue-naive patients, the assay proved to be a useful tool in detecting minor variant populations before the initiation of the treatment. These observations need further evaluation with prospective studies before they can be implemented in daily practice.
Keywords: DNA, Viral; Drug Resistance, Viral; Genotype; Hepatitis B virus; Hepatitis B, Chronic; Humans; Mutation, Missense; Precision Medicine; Real-Time Polymerase Chain Reaction; Sensitivity and Specificity